ORGANISATIONAL LEARNING AS A KNOWLEDGE RETENTION STRATEGY IN SELECTED PUBLIC BROADCASTING CORPORATIONS IN THE SOUTHERN AFRICAN DEVELOPMENT COMMUNITY - Dewah, Peterson (Mousaion: South African Journal of Information Studies, 2016)
This article reports on a study that assessed the organisational learning activities for the purposes of retaining critical knowledge in three Southern African Development Community (SADC) public broadcasting organisations. The article reports the partial findings of a doctoral study that focused on analysing the knowledge retention strategies in three public broadcasting corporations, namely, the South African Broadcasting Corporation (SABC), Department of Broadcasting Services (DBS) and Zimbabwe Broadcasting Corporation (ZBC), in the SADC. The aim of the study was to establish how organisational learning strategy captured and retained knowledge in these public broadcasting corporations. A structured self-administered survey questionnaire was used to purposively sample 162 professionals and managers in the three organisations. The study concluded that through organisational learning the three public broadcasting organisations captured and retained knowledge but were limited by the lack of knowledge management officials. The study recommends the establishment of knowledge officers’ posts to manage the organisational knowledge and to implement sound mentorship programmes to assist learning in these organisations. While the Human Resources (HR) departments may be managing the training of individuals as a way of acquiring knowledge, the study further recommends that the management should provide HR with more funds to improve the learning culture that allows for innovation, continuous knowledge creation and transformation.